A case of upper extremity thrombosis in patient with ulcerative colitis - İbrahim Halil Turkbeyler and Taner Babacan and M. Sait Dağ and Musa Aydınlı and Orhan Zengin and M. Akif Sarıca and Abdurrahman Kadayıfcı (Turkish Journal of Gastroenterology, 2019)
-